Quercetin Significantly Inhibits the Metabolism of Caffeine, a Substrate of Cytochrome P450 1A2 Unrelated to CYP1A2*1C (−2964G>A) and 1F* (734C>A) Gene Polymorphisms. (15th June 2014) - Xiao, Jian; Huang, Wei-Hua; Peng, Jing-Bo; Tan, Zhi-Rong; Ou-Yang, Dong-Sheng; Hu, Dong-Li; Zhang, Wei; Chen, Yao
Abstract : Background . Quercetin is abundant in plants and human diets. Previous studies indicated that quercetin inhibited the activity of CYP1A2, and the combination of quercetin with the substrates of CYP1A2 might produce herb-drug interactions. This research aims to determine the effects of quercetin and the CYP1A2 gene polymorphisms, namely, CYP 1 A 2 * 1 C (−2964G>A) and 1 F * (734C>A), on the metabolism of caffeine. Method . The experiment was designed into two treatment phases separated by a 2-week washout period. Six homozygous individuals for the CYP 1 A 2 * 1 C / 1 F * (GG/AA) genotype and 6 heterozygous individuals for the CYP 1 A 2 * 1 C / 1 F * (GA/CA) genotype were enrolled in the study. Quercetin capsules (500 mg) were given to each volunteer once daily for 13 consecutive days, and after that, each subject was coadministrated 100 mg caffeine capsules with 500 mg quercetin on the 14th day. Then a series of venous blood samples were collected for HPLC analysis. Correlation was determined between pharmacokinetics of caffeine and paraxanthine with caffeine metabolite ratio. Results. Quercetin significantly affected the pharmacokinetics of caffeine and its main metabolite paraxanthine, while no differences were found in the pharmacokinetics of caffeine and paraxanthine between GG/AA and GA/CA genotype groups. Conclusion. Quercetin significantly inhibits the caffeine metabolism, which is unrelated to CYP 1 A 2 * 1 C (−2964G>A) and 1 F * (734C>A) gene polymorphisms.